2017
DOI: 10.1016/j.jaim.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic potential of methanolic and flavonoid-rich leaf extracts of Synsepalum dulcificum in type 2 diabetic rats

Abstract: BackgroundSynsepalum dulcificum is a plant indigenous to West Africa. The fruit is used to modify taste of foods to sweetness.ObjectivesThis study aims to investigate the antidiabetic potentials of both methanolic and flavonoid-rich leaf extracts of S. dulcificum (MSD and FSD respectively) in type 2 diabetic Wistar albino rats.Materials and methodsSixty three rats were randomly distributed into nine groups of seven animals each with group 1 serving as the normal control. Groups 2 to 7 were given 10% fructose i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 35 publications
2
28
0
1
Order By: Relevance
“…Studies have demonstrated flavonoids have a promising role preventing obesity-related diabetic complications due to their effectiveness increasing insulin secretion, reducing insulin resistance, and inhibiting hormone-sensitive lipase activity (Obafemi et al. 2017 ; Liu et al. 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated flavonoids have a promising role preventing obesity-related diabetic complications due to their effectiveness increasing insulin secretion, reducing insulin resistance, and inhibiting hormone-sensitive lipase activity (Obafemi et al. 2017 ; Liu et al. 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the in‐vitro anti‐oxidant activity of the fruit, leaves, and seeds of S. dulcificum has been studied and was responsible by phenolic compounds and polysaccharides (Du, Shen, Zhang, Prinyawiwatkul, & Xu, 2014; Njoku, Ubbaonu, Alagbaoso, Eluchie, & Umelo, 2015). The anti‐diabetic effect of the fruit and leaves of this plant were found in rats (Obafemi, Akinmoladun, Olaleye, Agboade, & Onasanya, 2017). The butanol extract of the fruit, aqueous fraction of seeds extract, and methanolic extract of leaves all possessed anti‐hyperuricemia (Shi et al, 2016), anticonvulsant (Jeremiah, Ilesanmi, & Ige, 2015), and anti‐cancer (Seong, Oyong, & Cabrera, 2018) activities, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoid mampu meregenerasi sel beta pankreas dan membantu merangsang sekresi insulin (Dheer and Bhatnagar, 2010). Selain itu, konsumsi flavonoid atau senyawa kaya flavonoid melindungi tubuh terhadap radikal bebas dan senyawa pro-oksidatif lainnya, sehingga mengurangi risiko diabetes (Obafemi et al, 2017). Antioksidan dapat ditemukan dalam berbagai sumber makanan.…”
Section: Pendahuluanunclassified